New Zealand's Production Structure: An International Comparison - Iris Claus; Kathy Li (New Zealand Government, The Treasury, 2003)
The purpose of this paper is to compare New Zealand's production structure in the mid-1990s to that in other OECD countries using input output analysis. Comparable inter industry transactions tables to the New Zealand data are available for Australia, Belgium, Denmark, Finland, Germany, Norway and the United Kingdom. The composition of total supply and value added is examined across countries. Backward and forward linkages, indices of industry interconnectedness, a value added production multiplier, a cumulated primary input coefficient for compensation of employees and a measure of import content of final demand output are calculated, taking into account direct and indirect transactions. New Zealand's industrial structure is broadly similar to that in other OECD countries. Some differences arise as certain industries are more important in some countries. New Zealand's exports appear to be more diversified and have a large value added content. Moreover, the return to capital, as measured by the share of gross operating surplus in value added, is high.
Keywords: C67; L16; O57; 330; Input output models; industry importance; production structure; inter industry dependencies; country comparisons